Genetic structure of southern populations of Hydrochoerus hydrochaeris (Rodentia: Caviidae) - González-Barboza, Matías; Bou, Nadia; Byrne, Soledad; Ignacio Túnez, Juan; Duarte, José Mauricio Barbanti [UNESP]; Cosse, Mariana (Oxford University Press (OUP), 2024)
The capybara (Hydrochoerus hydrochaeris) is a large semi-aquatic rodent with a broad distribution across South America. Although it is a relatively common and well-known species, there are few studies on its evolutionary history. Consequently, we decided to investigate the genetic diversity, population structure, and demographic history of capybaras, including new populations from its southern distribution range, by using a 226 bp fragment of the mitochondrial D-loop region. We found 16 haplotypes and populations, with moderate levels of haplotype and nucleotide diversity. In addition, the genetic structure analyses suggested high genetic divergence among populations, mainly among Pampean and Chacoan populations. We also found a consistent phylogeographical pattern with the distribution of main rivers. In agreement with palaeontological data, we propose two colonization pathways towards the south driven by main basins: Paraná-Paraguay and Uruguay-Atlantic.
Keywords: genetic diversity; mitochondrial DNA; Neotropical rodents; phylogeography; river basins